Management and the Computer in Information and Control Systems - Hodge Bartow; Hodgson Robert N (Mcgraw Hill Book Company, 1969)
Preface, Introduction, The''What'', The ''What'' of Management control, Control Functions, Management Control Systems, Management Control Systems, The ''How'', Basic Definitions and Stages of System Design, Applied Control Theory, Management System Elements or Building Blocks, The Concept of Mathematical Models, Dynamic Analysis and Simulation of Management Control Functions, Tools and Models, Applications, Marketing Management Information and Control System, An Inventory Control Process, Management Information and Control System for Process and Plant, A Management Information and Control System for Flat-rolled Steel Products, Conclusions and a Look at the Future, Conclusions and Forecast, A Selected Bibliography, Index.
Preface, Introduction, The''What'', The ''What'' of Management control, Control Functions, Management Control Systems, Management Control Systems, The ''How'', Basic Definitions and Stages of System Design, Applied Control Theory, Management System Elements or Building Blocks, The Concept of Mathematical Models, Dynamic Analysis and Simulation of Management Control Functions, Tools and Models, Applications, Marketing Management Information and Control System, An Inventory Control Process, Management Information and Control System for Process and Plant, A Management Information and Control System for Flat-rolled Steel Products, Conclusions and a Look at the Future, Conclusions and Forecast, A Selected Bibliography, Index.